The Current Status of the Alternative Use to Antibiotics in Poultry Production: An African Perspective - Letlhogonolo Andrew Selaledi; Zahra Mohammed Hassan; Tlou Grace Manyelo; Monnye Mabelebele (MDPI AG, 2020)
Over the years the growth and health of food-producing animals have been enhanced by the use of antibiotics. These have helped reduce on-farm mortalities, lower incidences of diseases and more importantly improve productivity. Generally, the utilization of antibiotics in feed has been reevaluated since bacterial pathogens have established and shared a variety of antibiotic resistance mechanisms that can easily be spread within microbial communities. Multiple countries have introduced bans or severe restrictions on the non-therapeutic use of antibiotics. This has therefore warranted the urgent need for alternatives. Africa is facing its own challenges as it has been reported to be one of the continents with the highest number of foodborne diseases with approximately 91 million related diseases and 137,000 death per annum. Stakeholder and policy direction has been put in place to curb this escalation; however, the problem persists. The use of alternatives has been recommended and some successfully used in other countries as well as Africa, including pro- and prebiotics and phytochemicals. This then leads to the core aim of this review which is to (1) determine the extent to which antimicrobial-resistant pathogens have affected Africa, (2) assess the current measures put in place by Africa to reduces antimicrobial resistance and finally (3) explore the alternative use of antibiotics in poultry production. Improved sanitary conditions and farm biosecurity are important alternatives that could be adopted by farmers instead of depending on antibiotic drugs for disease control and prevention.